Experimental Investigation on Strength and Failure Characteristics of Cemented Paste Backfill - Zhang, Zhihong; Li, Jiacheng (Frontiers in Materials, 2021)
The strength characteristics of cemented paste backfill (CPB) in mining areas are key control factors for the safety assessment of overlying strata. A series of experiments about uniaxial compression and triaxial compression were carried out to study the influence of cement content of filling slurry, curing age, and curing temperature on strength behavior of CPB specimens. The failure mechanism and damage feature of CPB have been investigated. The results show the following: (1) The uniaxial compressive strength of CPB specimens exhibits an upward trend with the increase of cement content and curing age. When the cement content is high, the uniaxial compressive strength increases sharply with increasing curing age. (2) The cohesion of CPB specimens increases with the increase of cement content of filling slurry, curing age, and curing temperature. The cohesion of CPB specimens with curing age 7 days and 14 days increases linearly with increasing cement content. At the later stage of curing age, the strength growth of high cement content backfill is significantly greater than that of low cement content. The internal friction angle of the filling increases slightly with increasing filling cement content, curing age, and curing temperature. (3) The shear strength of CPB specimens at curing age 7 days exhibits an upward trend with the increase of confining pressure, while the shear strength at 14 days and 28 days curing age decreases slightly as the confining pressure increases. (4) With the increase of cement content in backfill, the brittleness increases significantly when the backfill is damaged. The failure mode of CPB specimens changes from monoclinic section shear failure to X-type failure with increasing curing age, and the failure process is divided into four stages: pore compaction, linear elastic deformation, plastic deformation, and post-peak failure.